Antoine Lavoisier, the next crucial year, or The sources of his quantitative method in chemistry - Holmes, Frederic Lawrence (Princeton legacy library., 1998)
Through his development of quantitative experimental methods, the chemist Antoine Lavoisier (1743-1794) implemented a principle that many regard as the cornerstone of modern science: in every operation there is an equal quantity of material before and after the operation. The origin of Lavoisier's methods, however, has remained a missing piece in this remarkable episode of scientific history, perhaps because the talented young scientist himself was not prepared for the journey his discoveries would set before him. In this book, Frederic Holmes suggests that Lavoisier gradually came to understand the nature and power of his quantitative method during the year 1773, when he began to carry out a research program on the fixation and release of airs. Drawing upon Lavoisier's surviving laboratory notebooks, Holmes presents an engaging portrait of a scientist still seeking the way that would lead him to become the leader of one of the great upheavals in the history of science.Holmes follows Lavoisier day-by-day at work in his laboratory over a course of several months. The scientist's resourcefulness and imagination spring to life in this account, as does his propensity to make mistakes, which taught him as much as his successes. During the course of this odyssey, Lavoisier saw his early theory of combustion collapse under the weight of his own efforts to provide experimental evidence to support it. In compensation, he acquired a method and the hard-won experience on which he would later construct a more enduring theoretical structure.Originally published in 1997.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.